3D Forming of Paperboard: The Influence of Paperboard Properties on Formability. (11th December 2013) - Vishtal, Alexey; Hauptmann, Marek; Zelm, Roland; Majschak, Jens‐Peter; Retulainen, Elias
<x xml:space="preserve">Abstract</x> Paper and paperboard are widely used in various types of packaging. Paper‐based packaging is a recyclable, biodegradable, renewable and sustainable product, which gives it certain advantages over most plastic‐based packaging materials. Although paper‐based packaging, in some areas, lacks attractiveness in terms of visual appearance, 3D forming is an important method for producing advanced shapes from paper and paperboard, suitable, for instance, for modified atmosphere packaging. That said, very little is known about the deformations experienced by paper‐based materials in 3D forming. Understanding the role played by the mechanical properties of paper and paperboard in the 3D forming process is key to improving performance. This paper presents experimental results obtained using three different forming devices designed to be used with paper‐based materials and links the formability data with specific mechanical properties of the paperboard samples. Paperboard properties that were found to correlate with formability were as follows: compressive strength and strain, tensile strain, paper‐to‐metal friction and out‐of‐plane stiffness. The requirements for formability are different for the fixed blank forming process and sliding blank forming process. Copyright © 2013 John Wiley & Sons, Ltd.